2021
DOI: 10.1038/s41586-021-03950-0
|View full text |Cite
|
Sign up to set email alerts
|

A multimodal cell census and atlas of the mammalian primary motor cortex

Abstract: Here we report the generation of a multimodal cell census and atlas of the mammalian primary motor cortex as the initial product of the BRAIN Initiative Cell Census Network (BICCN). This was achieved by coordinated large-scale analyses of single-cell transcriptomes, chromatin accessibility, DNA methylomes, spatially resolved single-cell transcriptomes, morphological and electrophysiological properties and cellular resolution input–output mapping, integrated through cross-modal computational analysis. Our resul… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
247
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 412 publications
(258 citation statements)
references
References 132 publications
10
247
1
Order By: Relevance
“…L2/3 cells have local axons branching in L2/3 and downward into L5, whereas L4 cells have local axons mainly projecting up to L2/3 68 . We also found 4 cells from MOp and MOs with these L4-like features -minimal apical dendrites and upward-projecting local axons, suggesting that these are the L4-like cells located in motor cortex 69 that can also be identified transcriptomically 70 . Consistent with prior notion 67 , all but two SSp L4 cells have only local axons but no long-range projections.…”
Section: Articlementioning
confidence: 62%
“…L2/3 cells have local axons branching in L2/3 and downward into L5, whereas L4 cells have local axons mainly projecting up to L2/3 68 . We also found 4 cells from MOp and MOs with these L4-like features -minimal apical dendrites and upward-projecting local axons, suggesting that these are the L4-like cells located in motor cortex 69 that can also be identified transcriptomically 70 . Consistent with prior notion 67 , all but two SSp L4 cells have only local axons but no long-range projections.…”
Section: Articlementioning
confidence: 62%
“…Over the past century, numerous studies have reported a great variety of cells in the mouse brain according to their morphological, electrical, and molecular features. Several groups such as the BRAIN Initiative® have launched ambitious projects to undertake a comprehensive census of all brain cells, determining their molecular, structural and functional properties [1][2][3][4]. Building a catalogue of the vast diversity of neuron types in the brain is a challenge for modern neuroscience.…”
Section: Introduction 1state Of the Artmentioning
confidence: 99%
“…Notably, thick-tufted layer V pyramidal neurons are a heterogeneous class of cells, but are morphologically different from their neighboring VENs ( Watson et al, 2006 ; compare with Ramaswamy and Markram, 2015 ; Cembrowski and Spruston, 2019 ; Rasia-Filho et al, 2021 ); see also comments on the likely coexistence of discrete and continuous variations that underlie cell-type diversity in BRAIN Initiative Cell Census Network (BICCN), 2021 . VENs emerge mainly after birth, increase in number until age 4 years ( Allman et al, 2005 ), and can be susceptible to alterations in some neuropsychiatric disorders (as described below).…”
Section: Discussionmentioning
confidence: 99%